One step microwave synthesis and magnetic properties of Co3O4 octahedrons - Zhang, Ping (2013)
Synthesis of nanocrystals with highly symmetric microstructure is a well-known challenge in many fields of science and technology. In this work, Well-defined uniform Co3O4 octahedrons were synthesized via a simple one step microwave reaction, in which different carbon materials were introduced acting not only as secondary heater, but also as morphology directing agent. The crystal-structure and shape of the samples are examined systemically by using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and high-resolution transmission electron microscopy (HRTEM). The octahedral Co3O4 obtained by carbon nanotubes (CNTs) assisting microwave process exhibited a weak ferromagnetic property. Its saturation magnetization values (Ms) and coercivity (Hc) values are 234.25 emu/g and 73.513 Oe, respectively.